Yes, in my backyard (YIMBY) and yours, too: women entrepreneurs’ leadership for a sustainable future of a small Japanese town - Helgeson, Jennifer; Omoto, Reiko; Kobayashi, Rika; Murao, Tomoko; Takeuchi, Maki; Watanabe, Mariko; Li, Bojie; Chabay, Ilan (Mitigation and adaptation strategies for global change, 2025)
We describe and discuss the narratives and backgrounds of four female entrepreneurs in a small rural town in Japan (Chizu, Tottori prefecture) who are working to foster emergent cultures of sustainability. The narratives concern their individual and group paths towards an entrepreneurial ecosystem that functions in tandem with the local socio-ecological system (SES) in strengthening the long-term vitality of a rural town. This paper was developed from the individual and collective narratives of these women entrepreneurs (all co-authors of this paper) which reflect their efforts to foster dialogues and form a community of purpose that enlists and expands upon a pre-existing movement of “small, lively communities” ( ikita chiiona komyunitii ) and the “zero-to-one movement” in Chizu Okada (Contemp Japan 34:210-227, 2022). The narratives connect not only to changing demographics in other small, rural communities in Japan and across the world, but also to women taking the initiative to actively engage economically, socially, and politically, despite cultures that have not usually been supportive of women’s initiatives and activist roles. In this paper, we highlight the importance of local initiatives led by women to build and share visions for sustainable futures for their communities. We explore narratives that reflect impacts of acute shocks and chronic stressors on the community (e.g., extreme weather events, as well as climate change and the COVID-19 pandemic) and express visions of sustainability. These narratives of a community as an integral part of its ecosystem influence the process of making decisions to mitigate or adapt to improve the well-being of the community for present and future generations. The women’s group and the individual women within the group hold visions of community sustainability goals that largely fit within Chizu’s culture, as it has been over the last several decades. However, the unique pathway(s) and futures-oriented thinking of these women differ in some ways from social norms in Japan. This distinction is especially notable as a change from, as well as beneficiary of the “zero-to-one movement” Okada (Contemp Japan 34:210-227, 2022). This was a very important and influential decades-long effort to revitalize Chizu, an effort largely organized and operated by men in authority in the area. Thus, there is tension within the complex system that includes entrepreneurial ecosystems and SES functioning within Chizu and the aspiration for forming a culture of sustainability. This paper offers a window into a local effort that can inspire action in other communities to shape constructive responses to a changing climate, changing demographic, and changing role for women acting to support the multi-generational well-being of the community in its socio-ecological system. Understanding the efforts of individual citizens for environmental sustainability and in support of the vitality of their community in the small town of Chizu, Japan may help understand the potential for similar efforts in other communities.